2020
DOI: 10.1177/1077546320976962
|View full text |Cite
|
Sign up to set email alerts
|

Study on the vibration isolation performance of an open trench–wave impedance block barrier using perfectly matched layer boundaries

Abstract: One of the problems associated with vibration pollution is ground vibration. In view of the isolation of objects protected from ground-transmitted vibrations, a novel type of vibration isolation barrier, an open trench–wave impedance block, is proposed. Based on the perfectly matched layer absorbing boundary, the two-dimensional finite element method in the frequency domain is used to investigate the vibration isolation performance of the open trench–wave impedance block barrier system for reducing the vibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Sarka et al [10] investigated the efficiency of using sand crumb rubber mixture for vibration isolation. Zhou et al [11] found that the vibration isolation performance of the open trench-wave impedance block barrier system can reduce the vibration generated by a vibration source. 3D FEM model was constructed by Kontoni et al [12] to study the train-induced vibrations on a nearby high-rise building.…”
Section: Introductionmentioning
confidence: 99%
“…Sarka et al [10] investigated the efficiency of using sand crumb rubber mixture for vibration isolation. Zhou et al [11] found that the vibration isolation performance of the open trench-wave impedance block barrier system can reduce the vibration generated by a vibration source. 3D FEM model was constructed by Kontoni et al [12] to study the train-induced vibrations on a nearby high-rise building.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al (2019), Zhou et al (2016), and Jiao et al (2018) analyzed the vibration isolation effect of the WIB made of geofoam sandwich and concrete-water-concrete composite vibration isolation barrier, and proved that the combined vibration isolation effect was better than that of single-layer WIB. Zhou et al (2020) analyzed the vibration isolation effect of the open trench-WIB barrier, the results show that the open trench-WIB barrier combines the advantages of the open trench and the WIB, and can effectively control the ground vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Herbut (2020) research on the vibration isolation effect of the open trench by finite element method from the view of reducing the vertical and horizontal components of vibration, the vibration isolation effect of the open trench on horizontal displacement is better than that on vertical displacement. Zhou et al (2022) present a novel wave barrier (open trench-wave impedance block barrier) by considering the respective advantages of the open trench and wave impedance block. The novel wave barrier has a better isolation effect for the vibration in the low-frequency range through finite element analysis.…”
Section: Introductionmentioning
confidence: 99%